Methotrimeprazine for the management of End-Of-Life Symptoms in Infants and Children. Issue 3 (September 2013) - Hohl, Christopher M.; Stenekes, Simone; Harlos, Michael S.; Shepherd, Erin; McClement, Susan; Chochinov, Harvey Max
Objective: This retrospective chart review assessed the efficacy, dose, and safety of methotrimeprazine in palliating end-of-life symptoms in children and infants. Methods: A retrospective chart review was conducted of 18 hospitalized pediatric patients who were treated with methotrimeprazine in their last two weeks of life. Data collected included age, diagnosis, symptoms, methotrimeprazine dose, route, efficacy, and any documented adverse effects. Results: Patients' ages ranged from 16 days to 17 years. Underlying conditions included malignancies, trauma, and various neurodegenerative and congenital diseases. All patients (n=18) were treated for symptoms of agitation, delirium, or restlessness. Most patients also experienced respiratory secretions/congestion (n=15), pain (n=13), and/ or dyspnea (n=9). Less common symptoms included nausea/emesis (n=5) and spasticity (n=1). Methotrimeprazine dosages ranged from 0.02 mg/kg/dose to 0.5 mg/kg/dose. Routes of administration included intravenous (n=13), oral/gastrostomy tube (n=6), or subcutaneous (n=4). Sedation (n=6) was the only documented adverse effect, although when agitation was present, this was potentially an intended and perceived-to-be-beneficial effect. Conclusion: Methotrimeprazine, an old drug with diverse receptor activity and multiple routes of administration, appears to be an effective tool in treating complicated end-of-life symptoms in children and infants. This study provides a foundation for analysis with prospective and comparative trials, which may further quantify its benefit.